Modern contraception usage and body weight change among women in Kota Bharu Bharu, 2013-2014 - Ibrahim, Hafizah (2016)
Background of the study: Contraception is not widely practised in Malaysia. Among the reasons for reluctance and discontinuation of contraceptive use include experience with adverse effects for example weight gain especially for hormonal users. Objectives: This study aimed to determine the types of modern contraceptive methods usage, the associated factors for hormonal contraceptive use and to compare the body weight change between hormonal user and non-hormonal user among women seeking family planning services in Kota Bharu health clinics in 2013-2014. Methodology: This study was a retrospective cohort study. Three-hundred-eighty women who used the same contraceptive method for 12 months in Kota Bharu health clinics were included in this study. Data were obtained from the Kad Perancang Keluarga (PKW 1 (a)/06) that were available in all the health clinics. Multiple logistic regression was used to determine the factors associated with hormonal contraceptive use and ANCOVA was used to compare the mean body weight change between hormonal and non-hormonal users. Results: The commonest methods used were hormonal methods (89.5%); combined contraceptive pills (44.2%), progestogen-only pills (13.7%) and injections (31.6%) as compared to non-hormonal methods (10.5%) [condoms (6.6%) and intrauterine device (3.9%)]. After adjusting for other variables, age of women and experience with adverse effect were the significant factors whereby with increment in age of women, the odds of using a hormonal method decreased (OR 0.92, 95% CI 0.87, 0.97, p-value 0.005) and with experience of adverse effect, the odds of women using hormonal methods decreased (OR 0.14, 95% CI 0.06, 0.33, p-value <0.001). The mean weight change among hormonal users (Adjusted mean 2.85, 95% CI 2.45, 3.24) were significantly higher from non-hormonal users (Adjusted mean 0.46, 95% CI -0.73, 1.65; p-value <0.001) after controlling for age, household income, number of pregnancies and baseline BMI. Conclusion: Majority of the women used hormonal contraceptive methods. The significant associated factors were age of women and experience with adverse effect. Mean weight changes among women using hormonal methods were significantly higher than those using non-hormonal contraceptive methods. Counselling should include the explanation regarding weight gain as a possible adverse effect for hormonal users, and more focus on younger women and first time users. Keywords: Modern contraception, weight changes, women of reproductive age, associated factors, outcome